2018
DOI: 10.1128/jvi.00415-18
|View full text |Cite|
|
Sign up to set email alerts
|

Pigs Lacking the Scavenger Receptor Cysteine-Rich Domain 5 of CD163 Are Resistant to Porcine Reproductive and Respiratory Syndrome Virus 1 Infection

Abstract: Porcine reproductive and respiratory syndrome (PRRS) virus (PRRSV) is the etiological agent of PRRS, causing late-term abortions, stillbirths, and respiratory disease in pigs, incurring major economic losses to the worldwide pig industry. The virus is highly mutagenic and can be divided into two species, PRRSV-1 and PRRSV-2, each containing several subtypes. Current control strategies mainly involve biosecurity measures, depopulation, and vaccination. Vaccines are at best only partially protective against infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 49 publications
4
107
1
1
Order By: Relevance
“…The resulting animals were completely resistant to PRRSV infection and maintained the biological functions associated with the remaining domains of CD163 (Burkard et al, 2017;Burkard et al, 2018).…”
Section: Pigsmentioning
confidence: 99%
“…The resulting animals were completely resistant to PRRSV infection and maintained the biological functions associated with the remaining domains of CD163 (Burkard et al, 2017;Burkard et al, 2018).…”
Section: Pigsmentioning
confidence: 99%
“…Based on this information, genome-edited pigs with a disruption in the CD163 gene were produced by CRISPR, conferring resistance to PRRSV infection. CD163 edited piglets, reported in two different projects in US and Scotland, were completely resistant to North American and European PRRSV strains [52,53]. The authors reported that the animals Table 1 Pregnancy outcomes after zygote microinjection with CRISPR/Cas system of in vitro produced embryos transferred fresh or subjected to vitrification in sheep (unpublished data).…”
Section: Disease-resistant Animalsmentioning
confidence: 99%
“…With the advance of CRISPR/Cas-based genome editing, specific gene-knockout pigs can be generated rapidly. The studies show that the pigs lacking either CD163 cellular receptor for PRRSV or the scavenger receptor cysteine-rich domain 5 (SRCR5) of CD163 become resistant to both PRRSV-1 and PRRSV-2 infections (Burkard et al, 2018;Prather et al, 2017;Whitworth et al, 2016;Yang et al, 2018). Such a gene-editing technology will allow generating immune-associated gene-deletion phenotypes, and genome-modified pigs will be valuable tools to study the basis for pathogenesis.…”
Section: Current Challenges and Future Research Directionsmentioning
confidence: 99%